The Future of Drug Discovery Who Decides Which Diseases to Treat? - Bartfai, Tamas; Bartfai, Tamas; Lees, Graham V. (Elsevier Science, 2013)
The Future of Drug Discovery: Who decides which diseases to treat? provides a timely and detailed look at the efforts of the pharmaceutical industry and how they relate, or should relate, to societal needs. The authors posit that as a result of increasing risk aversion and accelerated savings in research and development, the industry is not developing drugs for increasingly prevalent diseases, such as Alzheimer$1 (Bs disease, untreatable pain, antibiotics and more. This book carefully exposes the gap between the medicines and therapies we need and the current business path. By analyzing the situation and discussing prospects for the next decade, the The Future of Drug Discovery is a timely book for all those who care about the development needs for drugs for disease. This thought-provoking book is the first to: provide an in-depth, broad perspective on the crisis in drug industry expose the disconnect between what society needs and what the drug companies are working on analyse and project over 10 years into the future explain what it means for scientists and society determine what is needed to be done to make sure that the industry responds to society's needs, remains commercially attractive and answers the question as to who decides which diseases to treats